The Impact of Supervision on Teacher Preparation and Behavior: A Case Study of Public Elementary Schools in The Diponegoro Cluster, Punggelan District, Banjarnegara - Teguh Raharjo (Proceedings Series on Social Sciences & Humanities, 2025)
Education is a fundamental aspect of human life, providing the foundation for the development of human resources. Teacher competence, including pedagogical, personality, professional, and social skills, plays a crucial role in shaping students’ outcomes. Teachers are responsible not only for delivering knowledge but also for fostering students' character, learning ethos, and readiness for future challenges. The principal's role in organizing quality education is paramount, particularly through supervision. Supervision can enhance teachers' competence, improve classroom management, and strengthen the relationship between teachers and principals. This study investigates the comparison between teachers who receive supervision and those who do not, focusing on the impact of supervision on teacher preparation and behavior. The research adopts a qualitative descriptive approach using a case study method. Data was collected through interviews, observations, and document studies from five public elementary schools in the Diponegoro cluster, Punggelan District, Banjarnegara. The results provide insights into how supervision influences teacher performance and its role in optimizing student learning outcomes.